Решить примеры
-р(а-b)
3а*(а*b+4)
(5-2a+a2)(4а2-3а-1)

miaamkom1 miaamkom1    3   22.01.2020 19:31    0

Ответы
dhdhfjd55 dhdhfjd55  11.10.2020 02:35

-р*(а-b)=-ap-p*(-b)=-ap+bp

3a*(a*b+4)=3a*ab+3a*4=3a²b+12a

(5-2a+a2)(4a2-3a-1) (уже печатал на ПК и скринил т.к. устал печатать).


Решить примеры -р(а-b) 3а*(а*b+4) (5-2a+a2)(4а2-3а-1)
Решить примеры -р(а-b) 3а*(а*b+4) (5-2a+a2)(4а2-3а-1)
Решить примеры -р(а-b) 3а*(а*b+4) (5-2a+a2)(4а2-3а-1)
Решить примеры -р(а-b) 3а*(а*b+4) (5-2a+a2)(4а2-3а-1)
ПОКАЗАТЬ ОТВЕТЫ
Юшут Юшут  11.10.2020 02:35

Пошаговое объяснение:

-р(а-в)=-ар+вр

=3а^2b+12a

=20a^2-15a-5-8a^3+6a^2+2a+4a^4-3a^3-a^2=4a^4-11a^3+25a^2-13a-5

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика